2018
DOI: 10.1016/j.ijer.2018.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of proficiency on Vietnamese EFL learners’ engagement in peer interaction

Abstract: To expand previous interaction research that investigated only the impact of proficiency on occurrence of language related episodes or pair dynamics, this study explored the effect of proficiency on a range of cognitive, social and emotional features of interaction through the lens of engagement. Fifteen core EFL learners interacted with peers of higher and lower proficiency to complete picture sequencing tasks. The core learners' degree of engagement when interacting with the lower and the higher proficiency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…Xu (2019) shows an argument against the oversimplification of Chinese students as rote learners because they make efforts to show a higher level of reflective learning and engage with a deeper understanding of knowledge. Vietnamese students, in accordance with this change, attempt to become more engaged and demonstrate autonomy in learning when they are given these educational opportunities (Dao & McDonough, 2018;Pham & Iwashita, 2018).…”
Section: E-peer Feedback and Confucian Values In Vietnammentioning
confidence: 94%
“…Xu (2019) shows an argument against the oversimplification of Chinese students as rote learners because they make efforts to show a higher level of reflective learning and engage with a deeper understanding of knowledge. Vietnamese students, in accordance with this change, attempt to become more engaged and demonstrate autonomy in learning when they are given these educational opportunities (Dao & McDonough, 2018;Pham & Iwashita, 2018).…”
Section: E-peer Feedback and Confucian Values In Vietnammentioning
confidence: 94%
“…To explore the nature of emotional engagement, a questionnaire measuring learners' level of emotional engagement was administered three times after every five-minute interval of a 15-minute interaction. A communicative picture-sequencing task taken from previous research (Dao & McDonough, 2018) was used, in which learners discussed 10 pictures in a random order to form a meaningful story (for task instructions and pictures, see Appendix 1). The repeated delivery of the questionnaire was guided by the principle of Experience Sampling Method (ESM; see Csikszentmihalyi, 2014;Hektner et al, 2007;Hiver & Al-Hoorie, 2019;Zhou et al, 2021) whose primary purpose is to capture the learners' self-reported experience at regular intervals as it emerges and/or is directly perceived from one moment to the next.…”
Section: Designmentioning
confidence: 99%
“…Given their critical role in task performance (Lambert, 2017;Loewen & Sato, 2021;Mercer, 2019; see also Hiver et al, 2021aHiver et al, , 2021b and positive impact on second language (L2) learning such as lexical recall (Lambert et al, 2021; see also Fredricks et al, 2019;Reschly & Christenson, 2012), L2 learners' emotions have been a subject of investigation in recent L2 research. This research has investigated emotions either in relation to other constructs, such as motivation and willingness to communicate (see Dewaele, 2019;Dörnyei & Ryan, 2015), or as a subcomponent of a broader latent variable -learner engagement (see Dao, 2019;Dao & McDonough, 2018;Hiver et al, 2021a). While early L2 research primarily focused on negative emotions, such as L2 anxiety and unwillingness to communicate (see Horwitz, 2010;MacIntyre, 2017;Teimouri et al, 2019), more recent L2 research has focused on positive emotions, such as foreign language enjoyment in the classroom (Dewaele & Dewaele, 2017;Dewaele & MacIntyre, 2014, 2016, enjoyment and happiness in directed motivational currents (Ibrahim, 2016), and flow (Czimmermann & Piniel, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…English is viewed as a necessary tool for communication with the world beyond Iran's borders and as a means of providing access to information required for Academic technical and scientific texts in this globalized digital era (Dao & McDonough, 2018;Kiany et al, 2011;Zarrabi, 2017). Furthermore, English is viewed as cool and modern (prestigious) in Iran as well as a means of providing information for tourists and visitors who do not understand Persian (Sadeghi & Richards, 2015).…”
Section: The Status Of English In Iran In the Public Domainmentioning
confidence: 99%